The Impact of Social Media Attributes on Purchase Intention in the Saudi Foodservice - Al-Hadban, Nora; Almotairi, Mohammed (International Review of Management and Marketing, 2020)
This study aims to investigate the impact of social media attributes on customer purchase intention in the Saudi foodservice. It is a quantitative study based on the use of a questionnaire designed to fulfill the key purpose of this study. A judgmental sampling strategy is used to select the participants due to the wide population size. 380 questionnaires were collected and 357 were analyzed. SPSS.26 was used to analyze the data and to test the study hypotheses. The findings of this study revealed that social media attributes (perceived usefulness, perceived ease of use, critical mass and perceived playfulness) have has a positive impact on purchase intention. Keywords: Purchase Intention, Foodservice, Social Media Attributes, Saudi Arabia JEL Classifications: M40; M41 DOI: https://doi.org/10.32479/irmm.9719